A plasmonic photo-thermal probe for thermoablation of post-operative breast cancer cells. Issue 1 (1st January 2017) - Kan-Dapaah, Kwabena; Asimeng, Bernard Owusu; Kwofie, Samuel Kojo; Yaya, Abu
Abstract : Thermoablation of cancerous cells using probe-based strategies has received a lot of attention because it provides a localised minimally invasive strategy that minimizes injuries to collateral tissues. Although radiofrequency ablation is the most widely used probe-based method, skin injuries at the site of the grounding pad are a major complication that limits its efficacy. This paper presents a novel plasmonic photo-thermal probe that has the potential to achieve reasonable lesion sizes without skin burns. First, the concept and its embodiment are presented. Then, its performance is investigated using a 3-D finite-element method (FEM) model. The FEM model was tested for its validity using an analytical model. Lesions are shown to have an ellipsoidal shape and their sizes controlled by the length of the active tip of the probe. The comparison with the analytical model showed reasonably good agreement to within 2%. Our predictions demonstrate the feasibility of our novel probe to achieve reasonable lesion sizes as well as show that generated heat is localised.